Eksistensi Tradisi Ngejot di Lapangan Wirangbaya Bagi Masyarakat Lenek - Muhammad Ade Zaini Hasnan P; Suud Suud; Nursaptini Nursaptini (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
This study was conducted with the following objectives (1) to examine the existence of the Ngejot tradition among the people of Lenek Village, East Lombok Regenc (2) to identify the social and cultural values contained within the Ngejot tradition practiced by the Lenek Village community and (3) to understand the symbolic meaning of the tradition in maintaining family and community ties in Lenek Village, East Lombok Regency.The research employed a qualitative approach with an ethnographic method. The data used consisted of both primary and secondary sources. The subjects of the study included traditional leaders, community figures, practitioners of the Ngejot tradition, and local residents directly involved in its implementation. The informants were cultural figures, village officials, and community members who possess relevant knowledge and direct experience related to the Ngejot tradition, including those who have witnessed the event at Wirangbaya Field. Data collection techniques included observation, interviews, and documentation. The data analysis process was carried out in three stages (1) data reduction (2) data presentation and (3) drawing conclusions. The validity of the data was tested using triangulation techniques, namely (1) source triangulation (2) technique triangulation and (3) time triangulation.The results of the study revealed three main findings regarding the implementation of the Ngejot tradition at Wirangbaya Field (1) the Ngejot tradition remains preserved and is continuously practiced as a cultural heritage passed down through generations in Lenek Village (2) the tradition embodies social and cultural values such as mutual cooperation, togetherness, and mutual respect among community members and (3) the symbolic meaning of Ngejot is reflected in the use of trays (dulang) and food offerings, which represent gratitude and unity within the community.